On an Autonomous Pulsar Observation–Based Timekeeping Method for Deep Space - Shibin Song; Xiaowei Jin; Haixia Wang (International Journal of Aerospace Engineering)
To provide autonomous and accurate time service for deep space missions, a pulsar observation–based timekeeping method is documented in this paper, which utilizes pulsars as the time information source. Firstly, the pulsar observation noise is remodeled as the combination of the Gaussian noise and colored noise, and the detailed expression of the colored noise is presented in the paper. An improved Grey model (GM) is proposed to describe the onboard clock evolution, which models the grey action quantity as a time-varying coefficient and attenuates the dependence of the model on the initial state. On the basis of the modified observation noise model and GM, an unscented Kalman filtering (UKF) is adopted to estimate the onboard clock error. Numerical experiments are conducted to analyze the validity of the proposed method and the impact of spacecraft positioning error and pulsar selection on the proposed method. The proposed method offers an autonomous solution for onboard timekeeping in deep space missions.